The Concept of Qur’an and Hadith as the Foundation for Shaping Children’s Character in the Toxic Language Era - Burhanudin Afandi; Mufatihatut Taubah; Faiz Farichah (Jurnal test, 2026)
The normalization of toxic language on digital platforms has triggered serious moral degradation in children, demanding a pedagogical response that goes beyond secular approaches. This research aims to reconstruct the concept of language ethics in the Qur’an and Hadith as a fundamental basis for the formation of children’s character. This research uses a qualitative approach with a library research design. The main data sources include the terminology of qawl in the Mushaf of the Qur’an and the authoritative books of Hadith (Kutub al-Sittah), supported by reputable journal literature as secondary data. Data analysis is carried out through theological interpretation and pedagogical synthesis to bridge normative texts with contemporary phenomena. The results of the study show three crucial findings: (1) The concepts of qawl sadīd, karīm, and layyin are not just norms of decency, but psychospiritual foundations that determine the integrity of character and validity of faith; (2) Exposure to toxic language is positively correlated with empathy deficits and increased emotional impulsivity in children based on findings from previous empirical studies; and (3) The internalization of prophetic language values through example (uswah) as documented in the analyzed literature and observed in educational best practices indicates a promising preventive-curative approach that appears more sustainable than regulatory measures alone in mitigating verbal aggression. Further experimental research is recommended to empirically measure the comparative effectiveness of these approaches.